2018
DOI: 10.3389/fnins.2018.00419
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Disease and Selected Risk Factors Disrupt a Co-regulation of Monoamine Oxidase-A/B in the Hippocampus, but Not in the Cortex

Abstract: Monoamine oxidase-A (MAO-A) and MAO-B have both been implicated in the pathology of Alzheimer disease (AD). We examined 60 autopsied control and AD donor brain samples to determine how well MAO function aligned with two major risk factors for AD, namely sex and APOE ε4 status. MAO-A activity was increased in AD cortical, but not hippocampal, samples. In contrast, MAO-B activity was increased in both regions (with a strong input from female donors) whether sample means were compared based on: (a) diagnosis alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 93 publications
1
29
0
Order By: Relevance
“…Iproniazid, another MAO inhibitor, is used as an antidepressant drug (Yáñez et al, 2012). Several mechanisms have been proposed to account for involvement of MAO in AD pathology such as cognitive dysfunction via destroying cholinergic neurons and the formation of Aß aggregation or NFTs (Thomas, 2000;Huang et al, 2012;Mousseau and Baker, 2012;Cai, 2014;Quartey et al, 2018). This is in line with the recent study reporting that selegiline suppressed GABA production from reactive astrocytes, and restores the synaptic plasticity, and learning and memory function in the AD model mice (Park et al, 2019).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Iproniazid, another MAO inhibitor, is used as an antidepressant drug (Yáñez et al, 2012). Several mechanisms have been proposed to account for involvement of MAO in AD pathology such as cognitive dysfunction via destroying cholinergic neurons and the formation of Aß aggregation or NFTs (Thomas, 2000;Huang et al, 2012;Mousseau and Baker, 2012;Cai, 2014;Quartey et al, 2018). This is in line with the recent study reporting that selegiline suppressed GABA production from reactive astrocytes, and restores the synaptic plasticity, and learning and memory function in the AD model mice (Park et al, 2019).…”
Section: Discussionsupporting
confidence: 58%
“…In another way, bupivacaine may act on AMP-activated protein kinase (AMPK), and subsequently activate the downstream of AMPK (Huang et al, 2014). Selegiline and iproniazid are inhibitors of monamine oxidase inhibitors (MAO) that are known to be implicated in the AD pathology (Thomas, 2000;Huang et al, 2012;Quartey et al, 2018) (Figure 5B). In this context, this approach can repurpose potential anti-AD drug candidates that may be further investigated.…”
Section: Drug Repositioning Analysis For Ad Drug Discoverymentioning
confidence: 99%
“…In vitro studies demonstrate that Aβ peptides (1-42, 25-35) damage mitochondrial membrane potential (ΔΨm), increase ROS and cause abnormal mitochondrial fragmentation in several cell lines and also in primary neuronal cultures (Barsoum et al, 2006;Cha et al, 2012). A recent study on Alzheimer's disease brains revealed a complex dysregulation of the activities of specific mitochondrial enzymes, monoamine oxidases A and B (MAO A and B) and further confirmed that mRNA, protein and activity of the MAOs varied independently (Quartey et al, 2018). These observations suggest a central role for mitochondria in neurodegeneration that warrants investigation.…”
Section: Introductionmentioning
confidence: 84%
“…Because of the production of hydrogen peroxide and induced oxidative stress, excessive MAO activity is regarded as a risk factor in AD (Quartey et al, 2018). Indeed, inhibition of MAO has been proposed as a treatment target in AD (Hroch et al, 2017; Naoi & Maruyama, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal MAO activity promotes the loss of monoamines and mitochondrial peroxidation in AD. The activity of hippocampal MAO was significantly increased in humans carrying ε4 allele of apolipoprotein E and in experimental mouse models of AD [186][187][188]. This enhanced MAO activity not only causes insufficient monoamines for neurotransmission, but also induces significantly higher levels of peroxidative stress in monoaminergic neurones via H2O2 production.…”
Section: Monoamine Oxidase Inhibits Mitochondrial Functioningmentioning
confidence: 99%